(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Computed tomography (CT) diagnostic exams are responsible for the highest dose values to the patients. Therefore, the radiation doses in this procedure must be accurate. For the dosimetry of CT beams, the radiation detector is usually a pencil-type ionization chamber. This type of dosimeter presents a uniform response to the incident radiation beam from all angles, which makes it suitable for such equipment since the X-ray tube executes a circular movement around the table during irradiation. However, there is no primary standard system for this kind of radiation beam yet. In order to search for a CT primary standard, an extrapolation chamber built at the Calibration Laboratory (LCI) of the Instituto de Pesquisas Energéticas e Nucleares (IPEN) was tested. An extrapolation chamber is a parallel-plate ionization chamber that allows the variation of its sensitive air volume. This chamber was used previously for low-energy radiation beams and showed results within the international recommended limits. The aim of this work is to perform some characterization tests (saturation curve, polarity effect, ion collection efficiency and linearity of response) considering the chamber depth of 1.25 mm in the radiation qualities for computed tomography beams at the LCI. The results showed to be within the international recommended limits.